A Generative Approach to the Instructed Second Language Acquisition of Spanish se. Issue 1 (18th April 2022) - Juffs, Alan; Fang, Shaohua
Abstract: This article focuses on the role of crosslinguistic patterns with verbs in the mapping of noun phrases/semantic roles to positions in morphosyntax, with a particular focus on second language (L2) development of Spanish se . The data set derives from high school learners of Spanish in the United States under broadly deductive and inductive learning treatments leading to explicit awareness. Using linear mixed effects modeling (LME) and binomial logistic regression, an analysis of high school learners from three schools (total n = 138) showed that learners based their acceptability judgments of aurally presented sentences and written production on verb classes proposed in formal linguistic theory. However, effects of the instructional intervention were limited to production data. No advantage for either deductive or inductive instruction was identified. The data show a clear role for formal linguistic categories in explaining patterns in the data. Implications for fine‐tuning instructional intervention and testing of verb classes are discussed. Abstract :